(untitled) (The Review of Diabetic Studies, 2025)
Fainting (syncope) is a common clinical and community health event that is often benign yet distressing, and in many cases preventable. Nutritional and physiological factors such as hypoglycemia, dehydration, and iron deficiency are among the most frequent non-cardiac causes of transient loss of consciousness, particularly in vulnerable populations including adolescents, older adults, and individuals with chronic conditions. Despite its high prevalence, fainting remains inadequately addressed from a preventive and educational perspective. This review aims to synthesize current evidence on preventable nutritional causes of fainting, highlight nursing-led prevention strategies, and outline evidence-based first aid measures for immediate management. A narrative review of recent literature was conducted using major health databases, focusing on studies published between 2015 and 2025. Findings indicate that early identification of nutritional risk factors, patient education, and routine nursing assessment play a critical role in reducing fainting episodes. Furthermore, appropriate first aid responses—such as proper positioning, hydration, and timely referral—are essential in minimizing complications and recurrence. This review underscores the importance of an integrated prevention–response approach that links nutrition, nursing practice, and first aid education to improve patient safety and public health outcomes.